2005
DOI: 10.1042/bj20050434
|View full text |Cite
|
Sign up to set email alerts
|

Insights into the quaternary association of proteins through structure graphs: a case study of lectins

Abstract: The unique three-dimensional structure of both monomeric and oligomeric proteins is encoded in their sequence. The biological functions of proteins are dependent on their tertiary and quaternary structures, and hence it is important to understand the determinants of quaternary association in proteins. Although a large number of investigations have been carried out in this direction, the underlying principles of protein oligomerization are yet to be completely understood. Recently, new insights into this proble… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(31 citation statements)
references
References 50 publications
1
30
0
Order By: Relevance
“…The first consists of homologous proteins with different quaternary structures, such as globins (49) and lectins (50). These proteins have conserved tertiary structures; however, utilizing different types of protein contacts, they can assemble into a variety of quaternary states, from dimers to oligomers containing as many as 144 subunits as in the case of Lumbricus terrestris erythrocruorin (51).…”
Section: Resultsmentioning
confidence: 99%
“…The first consists of homologous proteins with different quaternary structures, such as globins (49) and lectins (50). These proteins have conserved tertiary structures; however, utilizing different types of protein contacts, they can assemble into a variety of quaternary states, from dimers to oligomers containing as many as 144 subunits as in the case of Lumbricus terrestris erythrocruorin (51).…”
Section: Resultsmentioning
confidence: 99%
“…It is reported that the formation of different PTX quaternary structures is due to differences in interface residues. For instance, the interface sites of decameric frog PTX are different from those of pentameric human PTXs (Brinda et al, 2005). According to the sequence comparison among hCRP, hSAP, reported pentameric fish PTXs and Dare-CRP, conserved interface sites such as Lys119 (in hCRP) are observed in pentameric PTXs.…”
Section: Discussionmentioning
confidence: 99%
“…How lectins form homodimers has been the subject of intense research. In some cases, such as plant lectins, specific signature sequences have been identified to explain the different modes of association implicated in the formation of homodimers (69). Each human galectin has its own sequence signature, which excludes most of the residues found in the signature sequence of the plant lectin interface.…”
Section: Analysis Of the Prototypic Galectin Homodimer Interfacementioning
confidence: 99%